Methods to improve the quality of scientific research by students of the specialty «Biology' (Journal of Educational Sciences, 2016)
The article shows the main periods of research work carried out in the higher educational institutions in order to develop an interest in science among students in the field of natural science. Scientific specifiedperiod organization of work and direction of scientific research on the theme: “Study of bioecological features of fungi affecting vegetable crops.”Conduct research to determine species of fungi that cause damage to vegetablesand their seeds were harvested in the spring and part of the damaged vegetables in the vegetable store in the village Kaynar Karasai district of Almaty region. Work has been done to determine the morphologicalfeatures of fungi and microscopical analyzes. The analysis period, the organization of research work in order to build consensus about the specifics of scientific research at the leading progressive schools in the course ofresearch. Conducting research based on improving the quality of education,by joining research projects with the process of learning through the development of research methods and scientific knowledge on the developmentof future spetsiality.
Keywords: natural sciences; Мulti-week project; scientific research work; types of fungi; Allium cepa L.; Daucus carota L